Pattern of malocclusion in orthodontic patients at a tertiary care centre - Sharma, Bishnu Prasad; Desar, Bikash (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Malocclusion is the most common dentofacial abnormality in human population, which can cause dental caries, periodontal disease and aesthetic problems. It is closely related to psychosocial wellbeing. The prevalence of malocclusion varies among different age and ethnic groups. The aim of this study was to assess the pattern of malocclusion occurring in orthodontic patients.Method: A 4-year data from 14 Apr 2018 to 13 Apr 2022 were collected retrospectively by the principal investigator (PI) from the pre-treatment record and an acceptable study cast from the Dental Department at Patan Hospital, Patan Academy of Health Sciences. Angle’s classification of malocclusion was used to classify malocclusion. The collected data were entered, and statistical analysis was carried out by using SPSS version 25. Chi-square test was applied to test the significant differences. The comparison was made between male and female and age group 6-12 years and 13 years and above for the Angle’s classification.Result: A total of 384 patients included in the study, female patients were 263(68.5%). Prevalence for malocclusion was 267(69.5%) of Angle’s class I, while Class II and Class III were 111(28.9%) and 6(1.6%) respectively. The study revealed not statistically significant. Majority 372(96.9%) belong to 13 y and above age group while only 12(3.1%) belong to 6-12 y age group.Conclusion: Angle’s Class I malocclusion was most prevalent with the least common being Angle’s Class III malocclusion. No statistically significant relationship was found. Almost all subjects were 13 years and above age group.